Application of transposon insertion site sequencing method in the exploration of gene function in microalgae - Hu, Xiaobing; Fan, Yulong; Mao, Chengfeng; Chen, Hui; Wang, Qiang (Frontiers in Microbiology, 2023)
Microalgae are a large group of organisms that can produce various useful substances through photosynthesis. Microalgae need to be genetically modified at the molecular level to become “Chassis Cells” for food, medicine, energy, and environmental protection and, consequently, obtain benefits from microalgae resources. Insertional mutagenesis of microalgae using transposons is a practical possibility for understanding the function of microalgae genes. Theoretical and technical support is provided in this manuscript for applying transposons to microalgae gene function by summarizing the sequencing method of transposon insertion sites.